Currency Crises and Monetary Policy in an Economy with Credit Constraints: The No Interest Parity Case - U. Michael Bergman; Shakill Hassan (University of Copenhagen, Economic Policy Research Unit (EPRU), 2008)
This paper revisits the currency crises model of Aghion, Bacchetta and Banerjee (2000, 2001, 2004), who show that if there exist nominal price rigidities and private sector credit constraints, and the credit multiplier depends on real interest rates, then the optimal monetary policy response to the threat of a currency crisis is restrictive. We demonstrate that this result is primarily due to the uncovered interest parity assumption. Assuming that the exchange rate is a martingale restores the case for expansionary reaction - even with foreign-currency debt in firms' balance sheets. The effect of lower interest rates on output can help restore the value of the currency due to increased money demand.
Keywords: E51; F30; O11; 330; currency crises; foreigncurrency debt; balance sheets; interest parity; monetary policy; Währungskrise; Liquiditätsbeschränkung; Zinsparität; Geldpolitik; Makroökonomik; Theorie